2014
DOI: 10.1002/cpp.1902
|View full text |Cite
|
Sign up to set email alerts
|

Yoga‐Enhanced Cognitive Behavioural Therapy (Y‐CBT) for Anxiety Management: A Pilot Study

Abstract: Cognitive behavioral therapy is an effective treatment for generalized anxiety disorder (GAD), but there is still room for improvement. The aim of the present study was to examine the potential benefit of enriching cognitive behavioral therapy (CBT) with Kundalini Yoga (Y-CBT). Participants consisted of treatment resistant clients at a community mental health clinic. A total of 32 participants enrolled in the study and 22 completed the program. After the Y-CBT intervention, pre-post comparisons showed statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 44 publications
3
72
0
Order By: Relevance
“…There is additional evidence from similarly rigorous research that trait EI training has long‐term (lasting for at least 1 year) beneficial effects in terms of reducing perceived stress levels, somatic complaints, and even diurnal cortisol secretion, a biological marker for stress (Kotsou, Nelis, Gregoire, & Mikolajczak, ). Preliminary research with young adolescents has suggested that cognitive behavioral group‐work (Ruttledge & Petrides, ) or yoga interventions (McIlvain, Miller, Lawhead, Barbosa‐Leiker, & Anderson, ) can have positive effects on trait EI scores (see also Khalsa, Greiner‐Ferris, Hofmann, & Khalsa, ). Collectively, this evidence is important both for its practical consequences in people's lives and for what it implies about the causal effects of trait EI on a range of psychological and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is additional evidence from similarly rigorous research that trait EI training has long‐term (lasting for at least 1 year) beneficial effects in terms of reducing perceived stress levels, somatic complaints, and even diurnal cortisol secretion, a biological marker for stress (Kotsou, Nelis, Gregoire, & Mikolajczak, ). Preliminary research with young adolescents has suggested that cognitive behavioral group‐work (Ruttledge & Petrides, ) or yoga interventions (McIlvain, Miller, Lawhead, Barbosa‐Leiker, & Anderson, ) can have positive effects on trait EI scores (see also Khalsa, Greiner‐Ferris, Hofmann, & Khalsa, ). Collectively, this evidence is important both for its practical consequences in people's lives and for what it implies about the causal effects of trait EI on a range of psychological and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence supporting the efficacy of yoga in reducing anxiety in general [26, 27], there are few trials of yoga for GAD, none of which are randomized controlled trials. Of the currently published uncontrolled trials reporting efficacy of yoga for GAD, two employed a yoga breathing intervention [28, 29], one employed a yoga mantra practice [30], and one applied an intervention combining CBT and Kundalini yoga practices [31]. The Kundalini yoga study showed statistically significant improvements in state and trait anxiety, depression, panic, sleep and quality of life with strong effect sizes for state and trait anxiety [31].…”
Section: Introductionmentioning
confidence: 99%
“…Of the currently published uncontrolled trials reporting efficacy of yoga for GAD, two employed a yoga breathing intervention [28, 29], one employed a yoga mantra practice [30], and one applied an intervention combining CBT and Kundalini yoga practices [31]. The Kundalini yoga study showed statistically significant improvements in state and trait anxiety, depression, panic, sleep and quality of life with strong effect sizes for state and trait anxiety [31]. In light of the paucity of high quality clinical trials of yoga for anxiety disorders, methodologically rigorous research undertakings are warranted to extend our current knowledge about the empirical status of yoga for GAD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a current trend to medicalize yoga, thereby raising it to the status of therapeutic modality rather than a spiritual, health promotional preventative practice. Against this background, it is not surprising that yoga is used as a part of psychotherapy [2,3] or sometimes even as a stand-alone psychotherapeutic tool [4,5]. Parallel to this inclusion in practice, literature is emerging to justify it [6][7][8].…”
Section: Introductionmentioning
confidence: 99%